Inovasi pencahayaan alami untuk keberlanjutan ‎pendekatan desain bukaan pada bangunan hemat energi ‎Quantum Tower - Ramadhani, Asmaina Nur (Maliki Interdisciplinary Journal, 2023)
This article explores innovations in the use of natural lighting to achieve desired goals in building design. Special focus is given to the case study of Quantum Tower, an urban icon that implements an energy-saving approach. This research uses a qualitative approach to investigate design strategies that contribute to increasing natural lighting in buildings. Through in-depth analysis of the Quantum Tower design, this research method explores information from various sources, including interviews with the design team and direct monitoring of lighting performance in the building. The interesting research results show that the integration of specially glazed double-glazed windows and bright facades is a key factor in ensuring optimal penetration of natural light. The distribution of interior space is also a concern in creating an evenly lit environment. These findings confirm that the destructive design approach has a positive impact on energy efficiency, with reduced electricity consumption for artificial lighting. The Quantum Tower case study provides practical guidance for architects who wish to apply similar concepts in their building projects. It is hoped that this article provides valuable insight into the potential of applying natural lighting in creating environmentally and energy sustainable buildings.